2012
DOI: 10.7575/ijalel.v.1n.5p.176
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Oral Communication Skills for Engineers in Engineering Profession of Pakistan

Abstract: This paper is licensed under a Creative Commons Attribution 3.0 License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Similarly, Kassim and Ali [20] identified both productive skills as having the highest mean scores (at 4.2875) compared to both listening and reading skills. Furthermore, Kakepoto, Omar, Boon, and Igbal [21] reported that oral communication skills play a vital role for engineers, especially in a workplace that involves multiple stakeholders because it assists them to perform workplace jobs effectively and efficiently according to employer satisfaction. Also, Ramlan & Ngah [5] added that an engineer is often required to communicate not only with other engineers but also with co-workers from different departments as well as with upper-level management which do not have the same background.…”
Section: English Language Problems For Engineering Students In Indonesiamentioning
confidence: 99%
“…Similarly, Kassim and Ali [20] identified both productive skills as having the highest mean scores (at 4.2875) compared to both listening and reading skills. Furthermore, Kakepoto, Omar, Boon, and Igbal [21] reported that oral communication skills play a vital role for engineers, especially in a workplace that involves multiple stakeholders because it assists them to perform workplace jobs effectively and efficiently according to employer satisfaction. Also, Ramlan & Ngah [5] added that an engineer is often required to communicate not only with other engineers but also with co-workers from different departments as well as with upper-level management which do not have the same background.…”
Section: English Language Problems For Engineering Students In Indonesiamentioning
confidence: 99%
“…Furthermore, English is necessary to maintain international dialogues between countries, and to help countries keep up with changing standards of knowledge, technology and business. Communication in English plays an important role in digital work and industrialization (Kakepoto et al, 2012). Prichard and Nasr (2004) argued that English is the language of science and, therefore, indispensable in modern sciences.…”
Section: Emi-related Research To Datementioning
confidence: 99%
“…At the managerial level then it became clear how critical English language use is for the success of companies. As for individuals, poor or limited English ability will affect not only their job productivity, salary and promotion, but also develop their poor image at the workplace, as has been reported in Kakepoto et al (2012).…”
Section: Communication Issues Losing Face and Low Solidarity Relationshipsmentioning
confidence: 89%
“…The importance of oral communication skills has been identified in numerous research studies (Ab.Rahim, 2008;Adzmi, Bidin, & Ibrahim, 2009;Al-Tamimi & Shuib, 2010;Bhattacharyya, 2014;Chia-Jung, 1991;Chia, Johnson, Chia, & Olive, 1999;Kaewpet, 2009a;Kakepoto, Omar, Boon, & Iqbal, 2012;Mohamed et al, 2014;Moslehifar & Ibrahim, 2012;Radzuan & Kaur, 2011;Stapa, Murad, & Ahmad, 2014;Talif & Noor, 2009;Zaid & Kamarudin, 2011). If engineers work in a situation where English is a medium of communication, they are expected to use English both formally and informally.…”
Section: Oral Communication Skills In Englishmentioning
confidence: 99%
See 1 more Smart Citation